Studi Interaksi Simbolik Dalam Menelaah Makna Simbol Leuit (Lumbung Padi) Pada Masyarakat Adat Ciptagelar - Nugraha Sugiarta (Universitas Informatika dan Bisnis Indonesia, 2020)
The purpose of this research is to investigate the leuit (rice barn) as a cultural heritage and a symbol of life in the Ciptagelar traditional community. This research uses a qualitative method with a symbolic interactionism approach. The results show that the leuit can be understood as a way of viewing Sundanese culture that is believed by the Ciptagelar traditional community. This is stated through the concept of opat kalima pancer. This concept is an ancestral cultural heritage for the Ciptagelar traditional community. The Ciptagelar traditional community continue to maintain the existence of the leuit because leuit is a cultural heritage which is part of the universe that connects humans with God. This is related to the symbolization of life in the leuit. For the Ciptagelar traditional community, caring for rice is like caring for life. Therefore, rice is considered a human being. In the scientific realm, animatism is known, which is to believe that whatever is on earth, especially plants, has spirit and life. Based on this understanding, it is not an exaggeration to see rice as respected as humans. In the end, leuit exist as a home or resting place for rice. Leuit thus has a philosophical meaning as a sacred place that legitimizes the life of the Ciptagelar traditional community in their physical and mental dimensions.